Teacher Strategies for Aligning Learning Media with Grade 4 Students' Learning Styles - Cahyani, Eka; Gagaramusu, Yusdin B.M.; Wilade, Surahman; Zulnuraini, Zulnuraini; Guci, Ammar Abdullah Joni (Journal of Innovation and Research in Primary Education, 2025)
Effective alignment between instructional media and student learning styles represents a critical challenge in elementary education, yet limited empirical evidence exists regarding systematic teacher strategies for implementing such alignment in classroom practice. This descriptive qualitative study investigated teacher strategies for aligning instructional media with Grade 4 student learning styles at SD Inpres 1 Tondo, Palu, Indonesia. Data were collected from 24 students and one classroom teacher through VARK-based questionnaires, semi-structured interviews, systematic classroom observations, and document analysis. Learning style distributions were analyzed descriptively, while teacher strategies and implementation effectiveness were examined using thematic analysis following Miles and Huberman's framework. Visual learners comprised 58.3% of students, followed by combined visual-auditory preferences (16.7%), auditory learners (12.5%), multimodal learners (8.3%), and kinesthetic learners (4.2%). Three primary teacher strategies emerged: comprehensive diagnostic assessment of learning styles, systematic integration of multimodal media (projectors, textbooks, environmental resources), and adaptive content delivery based on subject matter and student responses. Classroom observations revealed that multimodal approaches achieved 91% student engagement compared to 82% for single-modality instruction, with kinesthetic learners showing particular improvement during hands-on activities.  The findings demonstrate that effective media alignment depends on multimodal integration rather than rigid matching of single media types to individual learning preferences. Results support multimedia learning theory while extending understanding of practical implementation strategies in resource-constrained contexts. The study contributes evidence-based approaches for teacher professional development and differentiated instruction practices, emphasizing the importance of systematic diagnostic assessment and flexible pedagogical adaptation.